Post-partum depression: From clinical understanding to preclinical assessments - Moreira, Lorrane K. S.; Moreira, Caroline V. L.; Custódio, Carlos H. X.; Dias, Matheus L. P.; Rosa, Daniel A.; Ferreira-Neto, Marcos L.; Colombari, Eduardo [UNESP]; Costa, Elson A.; Fajemiroye, James O.; Pedrino, Gustavo R. (Frontiers, 2023)
Post-partum depression (PPD) with varying clinical manifestations affecting new parents remains underdiagnosed and poorly treated. This minireview revisits the pharmacotherapy, and relevant etiological basis, capable of advancing preclinical research frameworks. Maternal tasks accompanied by numerous behavioral readouts demand modeling different paradigms that reflect the complex and heterogenous nature of PPD. Hence, effective PPD-like characterization in animals towards the discovery of pharmacological intervention demands research that deepens our understanding of the roles of hormonal and non-hormonal components and mediators of this psychiatric disorder.
Keywords: behavioral models; depression; pharmacological targets; post-partum; preclinical assessments